2018
DOI: 10.1159/000490232
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Function in Adults with Epilepsy and Treated with Carbamazepine

Abstract: Background: Epilepsy is a chronic medical disease and is associated with comorbid adverse somatic conditions due to epilepsy itself or its long-term treatment. Objectives: This study evaluated cochlear function in patients with idiopathic epilepsy and treated with carbamazepine (CBZ). Patients and Methods: Included were 47 patients (mean age = 34.56 ± 7.11 years and duration of illness = 17.84 ± 7.21 years) and 40 healthy subjects. They underwent pure-tone audiometry and transient evoked otoacoustic emission (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Relationships between cardiovascular diseases and severe tinnitus have been reported previously ( Nondahl et al, 2002 ; Stobik et al, 2005 ; Park et al, 2014 ), however, the mechanisms linking cardiovascular health and tinnitus are poorly understood. In a recent study, tinnitus was found to be twice as prevalent in patients with epilepsy than control subjects, and the authors argue that tinnitus may be related to the disease itself as well as to its long-term drug treatment ( Hamed and Oseilly, 2018 ). Moreover, both conditions are linked to cortical hyperexcitability ( Chai et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relationships between cardiovascular diseases and severe tinnitus have been reported previously ( Nondahl et al, 2002 ; Stobik et al, 2005 ; Park et al, 2014 ), however, the mechanisms linking cardiovascular health and tinnitus are poorly understood. In a recent study, tinnitus was found to be twice as prevalent in patients with epilepsy than control subjects, and the authors argue that tinnitus may be related to the disease itself as well as to its long-term drug treatment ( Hamed and Oseilly, 2018 ). Moreover, both conditions are linked to cortical hyperexcitability ( Chai et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%